New socio-environmental indicators for sustainability reports. Case: peruvian mining companies in Lima stock exchange - Astorga de la Cruz, Brandelt Jesus (2020)
Objective: Design complementary socio-environmental indicators of generation value as part of the Sustainability Reports for Peruvian mining companies listed on the Lima Stock Exchange in 2017. Method: The study had an exploratory and descriptive scope, and a mixed approach: qualitative and quantitative. The research design was cross-sectional and non-probabilistic sampling were used, for convenience of the researcher. Results: The research results bring new indicators for Peru mining companies. Thus, the following social indicators are proposed such as: the relationship between the accident frequency index and income; the relationship of citizen participation and registries number of complaints; the percentage of training hours linked to accident prevention; and the relationship between the mining tax and income. Regard to environmental indicators, the following are proposed: recycled water percentage versus the total water used, and hazardous waste percentage versus total waste. Conclusions: It concluded that the suggested complementary indicators could contribute to the generation value of Peru's mining companies.